2017
DOI: 10.1021/acs.oprd.7b00301
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Concise Multikilogram Synthesis of LPA-1 Antagonist BMS-986020 via a Tandem Borylation–Suzuki Procedure

Abstract: The process development for the synthesis of BMS-986020 (1) via a palladium catalyzed tandem borylation/Suzuki reaction is described. Evaluation of conditions culminated in an efficient borylation procedure using tetrahydroxydiboron followed by a tandem Suzuki reaction employing the same commercially available palladium catalyst for both steps. This methodology addressed shortcomings of early synthetic routes and was ultimately used for the multikilogram scale synthesis of the active pharmaceutical ingredient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Greener borylation conditions were recently developed by Molander in collaboration with Merck using tetrahydroxydiboron [B 2 (OH) 4 or BBA], which is approximately one-third of the MW of B 2 (pin) 2 and thus has much higher atom economy . This reagent was utilized on a 65 kg scale by Takeda in the synthesis of TAK-117 (Scheme ), with an impressive 0.05 mol % loading of the palladium catalyst …”
Section: Discussionmentioning
confidence: 99%
“…Greener borylation conditions were recently developed by Molander in collaboration with Merck using tetrahydroxydiboron [B 2 (OH) 4 or BBA], which is approximately one-third of the MW of B 2 (pin) 2 and thus has much higher atom economy . This reagent was utilized on a 65 kg scale by Takeda in the synthesis of TAK-117 (Scheme ), with an impressive 0.05 mol % loading of the palladium catalyst …”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these transformations still require elevated reaction temperatures (≥80 °C) and until recently, focused on the synthesis of pinacol esters utilizing bis­(pinacolato)­diboron (B 2 pin 2 ). In 2010, Molander and Dreher reported that tetrahydroxydiboron (B 2 (OH) 4 , bisboronic acid or BBA), , a greener diboron source, directly yields boronic acids in one step from the corresponding aryl halide utilizing Buchwald’s XPhos-Pd-G1 and XPhos-Pd-G2 precatalysts . As a follow-up study to address the high cost associated with palladium, Molander subsequently reported the nickel-catalyzed borylation of aryl halides and pseudohalides, accessing a variety of potassium (hetero)­aryltrifluoroborates (eq ).…”
mentioning
confidence: 99%
“…Many other examples regarding the synthesis of biologically interesting molecules or natural products employing domino processes catalyzed by palladium species, where no cyclizations were involved, are described in the literature …”
Section: Discussionmentioning
confidence: 99%